Tax policy in the global economy : selected essays of Peggy B. Musgrave - Musgrave, Peggy B. (Cheltenham, UK ; Northampton, MA : E. Elgar, 2002)
In this selection of her path-breaking work, she extends income tax analysis to the arena of multinational investment and introduces and develops the concept of tax equity among nations. Her work addresses the complex tax issues which arise in the case of cross-border investment, an area of increasing importance in an integrated world economy. The globalization of economies and the vast expansion of foreign investment has greatly increased the problems of international taxation. The author argues that cross-border tax issues should not be left to the destructive forces of tax competition but should be handled through coordinating measures of international tax agreements. Thereby tax distortions in the international flow of capital will be minimized while leaving countries free to determine their own tax structures. This book should prove valuable reading for economists, lawyers and policy makers concerned with the emerging world of multijurisdictional fiscal relations and how efficient and equitable solutions can be designed.
Includes bibliographical references and index.
oif 15/07/14, ijb 19/03/2019
Loan
Keywords: Taxation; Investments, Foreign; Finance, Public